Grading Aortic Stenosis With Mean Gradient and Aortic Valve Area: A Comparison Between Preoperative Transthoracic and Precardiopulmonary Bypass Transesophageal Echocardiography. Issue 1 (February 2017) - Whitener, G.; Sivak, J.; Akushevich, I.; Samad, Z.; Swaminathan, M.
Abstract : (Abstracted from J Cardiothorac Vasc Anesth, 30(5):1254–1259, 2016) In cardiac surgery, pre–cardiopulmonary bypass (pre-CPB) transesophageal echocardiography (TEE) is essential for intraoperative assessment and surgical guidance as findings can affect surgical decision making. While accurate interpretation of grading parameters during the pre-CPB period is essential, the validated mean gradient (PGm ) and aortic valve area (AVA) grading cutoffs for aortic stenosis (AS) originate from studies that used transthoracic echocardiography (TTE) in spontaneously ventilating patients.